FAKTOR YANG BERHUBUNGAN DENGAN KUNJUNGAN BALITA KE POSYANDU DI WILAYAH KERJA PUSKESMAS PAAL MERAH I - Hidayanti, Novia (Universitas Fort de Kock Bukittinggi, 2023)
The achievement of children under five who visited and weighed at Posyandu compared to all children under five (D/S) in Indonesia in 2022 was still below the target, which was 61.3% of the 80% targeted. The purpose of this study was to determine the factors associated with visits by children under five to the posyandu in the working area of the Paal Merah I Public Health Center, Jambi City in 2022. This study was a quantitative study with a cross-sectional research design through univariate and bivariate data analysis. The study was conducted from April to August 2022. The population in this study were all mothers who had toddlers as many as 518 people with a simple random sampling technique and totaled 30 people. This research was conducted through the interview method and using a questionnaire. The results showed that most of the respondents had low education, namely 20 respondents (66.7%), good knowledge, namely 23 respondents (76.7%), good motivation, namely 17 respondents (56.7%), good family support, namely 15 respondents. (50%), not actively visiting posyandu, namely 16 respondents (53.3 %). The results of the statistical test showed that the education variable had a p value of 0.007 and an OR value of 16,714, knowledge with a p value of 0.007 and an OR value of 2.556, motivation with a p value of 0.008 and an OR value of 13.2 and family support with a p value of 0.010 and an OR value of 11.0. It can be concluded that there is a relationship between education, knowledge, motivation and family support with visits to Posyandu under five. It is hoped that the results of this study can be used as information to further improve education, knowledge, motivation and family support so that posyandu visits can be further increased.